The Impact of Streptozotocin-Induced Diabetes on Testosterone Hormone and Androgen Receptor Expression and Correlation with Sperm Quality Impairment in Sprague Dawley Rats - Nazaruddin, Nazaruddin; Siregar, Tongku Nizwan; Sutriana, Amalia; Wahyuni, Sri; Armansyah, Teuku (Trends in Sciences, 2025)
The growing prevalence of type 2 diabetes mellitus (T2DM) has raised significant concerns about its detrimental effects on male reproductive health. Streptozotocin (STZ)-induced diabetic models, particularly when combined with a high-fat diet (HFD), effectively replicate key features of human T2DM, including hyperglycemia and subsequent reproductive dysfunction. This study investigates the impact of STZ with various doses in inducing diabetes on testosterone levels, androgen receptor (AR) expression, and semen quality in male Sprague Dawley rats. Twenty rats, aged approximately 2 months and weighing 200 - 250 g, were divided into 4 groups (n = 5). Each group received a single intraperitoneal injection of STZ at doses of 0 mg/kg BW (P0), 20 mg/kg BW (P1), 30 mg/kg BW (P2), and 40 mg/kg BW (P3), using 0.1 M citrate buffer (pH 4.5) as the solvent. On day 56, blood glucose levels (BGL) were significantly elevated (p < 0.05) in all treated groups, particularly in P3 (average BGL 196.0 ± 4.24 mg/dL), indicating successful DM induction. Testosterone concentration in P3 was significantly lower (0.18 ± 0.05 ng/dL) compared to other groups (p < 0.05). Additionally, sperm concentration, motility, and viability in P3 showed a significant decrease (p = 0.00), while sperm abnormalities significantly increased (p = 0.00). AR intensity score (IS) was markedly reduced in P3 compared to other groups (p < 0.01). Histopathological examination revealed necrosis and lysis in seminiferous tubules, interstitial tissue damage, and decreased quantity and quality of spermatogenic cells. These findings confirm that STZ at 40 mg/kg BW effectively induces hyperglycemia and causes significant disruptions in male reproductive parameters, including hormonal profiles, sperm characteristics, and AR expression. This outcome offers a reliable method for studying the reproductive consequences of DM and may serve as a platform for evaluating potential therapeutic strategies to mitigate DM-related infertility. HIGHLIGHTS This study demonstrates that STZ-induced hyperglycemia significantly reduces testosterone levels and androgen receptor expression in male Sprague Dawley rats. Elevated BGLs were strongly correlated with decreased sperm concentration, motility, and viability, and increased sperm abnormalities. Histopathological analysis revealed extensive testicular damage, including seminiferous tubule disruption and reduced Leydig and Sertoli cell populations. IHC findings confirmed downregulation of AR expression in diabetic rats, supporting the role of oxidative stress in reproductive dysfunction. The model provides a reliable platform to investigate the pathophysiology of diabetes-induced male infertility and evaluate potential therapeutic interventions. GRAPHICAL ABSTRACT